Reformasi Sistem Peradilan Militer Indonesia - Tiarsen Buaton; Agustinus Purnomo Hadi; Prastopo Prastopo; Ateng Karsoma; M. Ali Ridho (Penerbit Goodwood, 2024)
Purpose: Reform of the military justice system (criminal law enforcement) is essentially part of the idea of law reform. Law reform not only includes